2019
DOI: 10.1007/978-3-030-12612-4_24
|View full text |Cite
|
Sign up to set email alerts
|

EPIC: Efficient Private Image Classification (or: Learning from the Masters)

Abstract: Outsourcing an image classification task raises privacy concerns, both from the image provider's perspective, who wishes to keep their images confidential, and from the classification algorithm provider's perspective, who wishes to protect the intellectual property of their classifier. We propose EPIC, an efficient private image classification system based on support vector machine (SVM) learning, secure against malicious adversaries. EPIC builds upon transfer learning techniques known from the Machine Learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…The work also provides a simple easy-to-use API with a translator from Keras [51] to XONN. EPIC [52] demonstrates the use of transfer learning in the space of privacy-preserving machine learning while Quotient [53] takes the first steps in developing two party secure computation protocols for optimizers and normalizations. CrypTFlow [13] builds on SecureNN and uses trusted hardware to achieve maliciously secure protocols in a 3PC model.…”
Section: Privatementioning
confidence: 99%
“…The work also provides a simple easy-to-use API with a translator from Keras [51] to XONN. EPIC [52] demonstrates the use of transfer learning in the space of privacy-preserving machine learning while Quotient [53] takes the first steps in developing two party secure computation protocols for optimizers and normalizations. CrypTFlow [13] builds on SecureNN and uses trusted hardware to achieve maliciously secure protocols in a 3PC model.…”
Section: Privatementioning
confidence: 99%
“…P3 abort if the received values are inconsistent. 3 ) in the boolean world, if we can get the garbled shares of x = (m v ⊕λ v,1 ) and y = (λ v,2 ⊕λ v,3 ), parties can use the free XOR technique to compute the garbled shares of v locally. Each of x, y is possessed by two parties, enabling them to verifiably generate the garbled shares using the protocol Π G vSh .…”
Section: Offlinementioning
confidence: 99%
“…Proof: To see the correctness, it suffices to show that 3 ). Note that r = 2 d r t + r d where r t denoted the truncated value of r and r d denoted the last d bits of r. Then, Cost Comparison:…”
Section: Convmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature work has already shown that machine learning inferencing, upon which many fall detection systems rely, can be performed efficiently using MPC. This includes MPCbased image recognition using support vector machines (SVMs) [28] and remote rehabilitation treatment classification from patient data using decision trees [11].…”
Section: Introductionmentioning
confidence: 99%